The Determination of Filaggrin Gene Single Nucleotides Polymorphisms in Patients with Atopic Dermatitis - Narmandakh, Zolmunkh; Tulgaa, Khosbayar; Munkhbayar, Ariunaa; Dungubat, Erdenetsogt; Lkhamkhuu, Algirmaa; Tumurbaatar, Otgonjargal; Byamba, Khandsuren; Sandag, Tsogtsaikhan; Gunchin, Batbaatar (Central Asian Journal of Medical Sciences, 2017)
Objectives: The protein, filaggrin, is important in barrier function and epidermal differentiation facilitation. Filaggrin gene (FLG) mutations have been identified as the cause of ichthyosis vulgaris (IV), and certain mutations have been associated with atopic dermatitis (AD). We aimed to investigate genetic polymorphism of FLG in Mongolian AD patients. Methods: FLG mutations were determined using sequence analysis in 46 AD patients and 12 IV patients. Severity of AD was assessed using the Scoring Atopic Dermatitis (SCORAD) index. Allergen specific IgE were determined from serum. Filaggrin expression in skin punch biopsy samples of AD patients was investigated using immunohistochemistry (IHC). Results: Several single nucleotides polymorphisms (SNPs) (1150C>T, 1741A>T, 1791C>T, 2181C>G, 2191A>G, and 2263G>A) were demonstrated in AD patients using sequence analysis. Total IgE levels were significantly associated with age (p=0.03) and duration of disease (p=0.02). Presence of SNPs and mixed allergen specific IgE was significantly correlated (p=0.02); 2 SNPs were significantly associated with food allergen specific IgE levels (p=0.009). 2263G>A SNP was significantly correlated with food allergen specific IgE (p=0.003) and a history of atopic diseases (p=0.03). Conclusion: New mutations or genetic polymorphisms with ethnic characteristics may be detected among Mongolians.